2017
DOI: 10.1105/tpc.17.00364
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis WRKY46, WRKY54 and WRKY70 Transcription Factors Are Involved in Brassinosteroid-Regulated Plant Growth and Drought Response

Abstract: Plant steroid hormones, brassinosteroids (BRs), play important roles in growth and development. BR signaling controls the activities of BRASSINOSTERIOD INSENSITIVE1-EMS-SUPPRESSOR1/BRASSINAZOLE-RESISTANT1 (BES1/BZR1) family transcription factors. Besides the role in promoting growth, BRs are also implicated in plant responses to drought stress. However, the molecular mechanisms by which BRs regulate drought response have just begun to be revealed. The functions of WRKY transcription factors in BR-regulated pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
276
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 291 publications
(303 citation statements)
references
References 81 publications
(104 reference statements)
5
276
0
Order By: Relevance
“…Previous studies have revealed that one WRKY gene could function in several disparate signaling pathways. For example, AtWRKY70 functions in plant growth, drought response and cell death [52,53]. Interestingly, we found that the SiWRKY17 and SiWRKY43 was induced to highly express under waterlogging stress, while the orthologous genes of them, AtWRKY32 and AtWRKY29, was reported to respond to UV irradiation and heat stress, respectively.…”
Section: Identification Of Siwrky Genes Involved In Responses To Abiomentioning
confidence: 75%
“…Previous studies have revealed that one WRKY gene could function in several disparate signaling pathways. For example, AtWRKY70 functions in plant growth, drought response and cell death [52,53]. Interestingly, we found that the SiWRKY17 and SiWRKY43 was induced to highly express under waterlogging stress, while the orthologous genes of them, AtWRKY32 and AtWRKY29, was reported to respond to UV irradiation and heat stress, respectively.…”
Section: Identification Of Siwrky Genes Involved In Responses To Abiomentioning
confidence: 75%
“…We also measured BL and CS (a precursor of BL) contents in the transgenic apple line overexpressing MdWRKY9 and the control plants. Due to the low content of BL in apple plants, it was not detected, as in other species (Chen et al ., ). The content of CS in transgenic line 1 overexpressing MdWRKY9 (10.15 ng g −1 ) was only 68% that of the control (14.82 ng g −1 ) (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…We also measured BL and CS (a precursor of BL) contents in the transgenic apple line overexpressing MdWRKY9 and the control plants. Due to the low content of BL in apple plants, it was not detected, as in other species (Chen et al, 2017).…”
Section: Mdwrky9 Overexpression Reduces the Br Content In Transgenicmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on candidate gene association analysis, further research has indicated that OsLG3 plays a positive role in water deficit tolerance in rice by ROS (Xiong et al., ). RNA sequencing analysis of Arabidopsis has also revealed that transcription factors WRKY46 , WRKY54 , and WRKY70 play important roles in promoting BR‐mediated gene expression and inhibiting drought‐responsive genes (Chen et al., ). Additionally, the flowering repressor SHORT VEGETATIVE PHASE (SVP) is induced by drought stress and is associated with promoter regions of ABA catabolic pathway genes CYP707A1/3 and AtBG1 .…”
Section: Introductionmentioning
confidence: 99%